2020
DOI: 10.3390/nu12051450
|View full text |Cite
|
Sign up to set email alerts
|

Changed Amino Acids in NAFLD and Liver Fibrosis: A Large Cross-Sectional Study without Influence of Insulin Resistance

Abstract: Altered amino acid levels have been found in nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH). However, it is not clear whether this alteration is due to altered hepatic metabolism or insulin resistance. The aim of this study was to clarify the association among amino acid levels, fatty liver, and liver fibrosis while eliminating the influence of insulin resistance. NAFLD and liver fibrosis were diagnosed using transient elastography and subjects were divided into three groups: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…As discussed before, most of the dysregulated amino acids in this study are associated with insulin resistance suggesting that participants with T2D in this study are at high risk of developing NAFLD. In addition, a previous study revealed that high Glu levels had a significant pathological role in the development of liver fibrosis independently from insulin resistance (Hasegawa et al, 2020). In this study, Glu level was significantly higher in T2D and together with increased TG and LDL could increase the risk of future liver fibrosis as well as cardiovascular complications.…”
Section: Discussionsupporting
confidence: 48%
“…As discussed before, most of the dysregulated amino acids in this study are associated with insulin resistance suggesting that participants with T2D in this study are at high risk of developing NAFLD. In addition, a previous study revealed that high Glu levels had a significant pathological role in the development of liver fibrosis independently from insulin resistance (Hasegawa et al, 2020). In this study, Glu level was significantly higher in T2D and together with increased TG and LDL could increase the risk of future liver fibrosis as well as cardiovascular complications.…”
Section: Discussionsupporting
confidence: 48%
“…Apart from BCAA, we also identify a positive association between Ala and TG as several previous studies in non-diabetes (30,39). Ala plays a key role in the glucose-alanine cycle between tissues and the liver.…”
Section: Discussionsupporting
confidence: 79%
“…Besides, the associations were robust in the context of LDL-C, suggesting that abnormal amino Although the relationships between amino acids and lipid abnormality were yet completely clarified, their associations have been investigated in many studies. Compared with healthy controls, patients with abnormal BMI or non-alcoholic fatty liver disease have profound perturbation of amino acid metabolism (29,30). Several cross-sectional and longitudinal studies also showed that amino acid signature significantly predicted future hypertriglyceridemia in children (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the metabolite sub-networks of the HFD-derived LCGs Smim13 and Rapgef4 not only included BA, PC, LPC, and AC metabolites, but also their subgraphs were interconnected by an overlapping mixture of AA. An impaired AA metabolism was previously linked to NAFLD and liver fibrosis [ 26 , 27 ]. The third HFD sub-network was under the control of the LCG Inhbe and contained only AC which is known to be involved in fat metabolism, especially in the carnitine shuttle transporting long-chain fatty acids into mitochondria [ 28 ].…”
Section: Resultsmentioning
confidence: 99%